1966. Protection afforded by prior infection, vaccination, and hybrid immunity against symptomatic BA.1 and BA.2 Omicron infections. (15th December 2022) - Altarawneh, Heba N; Chemaitelly, Hiam; Ayoub, Houssein H; Tang, Patrick; Hasan, Mohammad R; Yassine, Hadi M; Al-Khatib, Hebah A; Smatti, Maria K; Coyle, Peter; Al-Kanaani, Zaina; Al-Kuwari, Einas; Jeremijenko, Andrew; et al.
Abstract: Background: Protection offered by five different forms of immunity, combining natural and vaccine immunity, was investigated against symptomatic SARS-CoV-2 infection from Omicron BA.1 or BA.2, and severe, critical, or fatal COVID-19 from BA.1 or BA.2, in Qatar, between December 23, 2021 and February 21, 2022. Methods: Six national, matched, test-negative case-control studies were conducted on a sample of 272, 861 PCR-positive tests and 669, 628 PCR-negative tests to estimate effectiveness of BNT162b2 (Pfizer-BioNTech) vaccine, mRNA-1273 (Moderna) vaccine, natural immunity due to prior infection with pre-Omicron variants, and hybrid immunity from prior infection and vaccination. Results: Effectiveness of prior infection alone against symptomatic BA.2 infection was 46.1% (95% CI: 39.5-51.9%). Effectiveness of two-dose BNT162b2 vaccination alone was negligible at -1.1% (95% CI: -7.1-4.6), but nearly all individuals received their second dose >6 months earlier. Effectiveness of three-dose BNT162b2 vaccination alone was 52.2% (95% CI: 48.1-55.9%). Effectiveness of hybrid immunity of prior infection and two-dose BNT162b2 vaccination was 55.1% (95% CI: 50.9-58.9%). Effectiveness of hybrid immunity of prior infection and three-dose BNT162b2 vaccination was 77.3% (95% CI: 72.4-81.4%). Meanwhile, prior infection, BNT162b2 vaccination, and hybrid immunity all showed strong effectiveness ( >70%) against severe, critical, or fatal COVID-19 due to BA.2. Similar patterns of effectiveness were observed for BA.1 and for the mRNA-1273 vaccine. Figure 1. Effectiveness of prior infection, vaccination, and hybrid immunity against symptomatic Omicron infection and against severe, critical, or fatal COVID-19 for the BA.1 (panels A and B, respectively) and BA.2 (panels C and D, respectively) subvariants in the BNT162b2-vaccine study. Figure 2. Effectiveness of prior infection, vaccination, and hybrid immunity against symptomatic Omicron infection and against severe, critical, or fatal COVID-19 for the BA.1 (panels A and B, respectively) and BA.2 (panels C and D, respectively) subvariants in the mRNA-1273-vaccine study. Conclusion: There are no discernable differences between BA.1 and BA.2 in the effects of prior infection, vaccination, and hybrid immunity. Vaccination enhances the protection of those with a prior infection. Hybrid immunity resulting from prior infection and recent booster vaccination conferred the strongest protection. Disclosures: Adeel A. Butt, MBBS, Gilead Sciences: Grant/Research Support.